Penelitian Retrospektif Pasien Skabies Berdasarkan Faktor Usia dan Jenis Kelamin di Poliklinik RS Pertamina Bintang Amin Periode 02 Januari 2016- 31 Desember 2018 - Retno Oktavia; Arif Effendi; Eka Silvia (Puslitbang Sinergis Asa Professional, 2021)
Scabies is a skin disease caused by infestation and sensitization to Sarcoptes scabiei var hominis. Scabies characterized by night itching, affecting a group of people, with a predilection spot in the skin folds that are thin, warm, and moist. Clinical symptoms can be seen polymorphy spread throughout the body. Scabies disease can be prevented by educating patients about scabies which are: disease course, transmission, how to eradicate scabies mites, maintaining personal hygiene, and procedures for applying drugs. Objective: To determine the prevalence of the incidence of scabies and the factors that influence the incidence of scabies based on age and sex at Pertamina Bintang Amin Hospital for January 2, 2016 - December 31, 2018. The type of research used in this research is a descriptive retrospective study by looking at the medical records of scabies patients at the Polyclinic of Skin and Venereal Diseases at Pertamina Bintang Amin Hospital, Bandar Lampung, 2 January 2016-31 December 2018. In this study, the results of the prevalence of scabies were 261 cases (9%) of 2924 patients with skin and venereal diseases for the period of January 2, 2016-31 December 2018 with the highest prevalence, namely in 2018 as many as 108 cases (11%) of 963 patients with skin and venereal diseases. Scabies can occur in women or men and children or adults. The results of this study indicate that most people who suffer from scabies are in the age group of 20-59 years as many as 128 cases (49%), and the most sexes suffer from scabies. Scabies, namely male, as many as 163 cases (62.5%).